2021
DOI: 10.3390/jpm11121274
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of C-Reactive Protein to Lymphocyte Ratio (CLR) in Emergency Department Patients with SARS-CoV-2 Infection

Abstract: (1) Introduction: According to recent studies, the ratio of C-reactive-protein to lymphocyte is more sensitive and specific than other biomarkers associated to systemic inflammatory processes. This study aimed to determine the prognostic value of CLR on COVID-19 severity and mortality at emergency department (ED) admission. (2) Methods: Between 1 March and 30 April 2020, we carried out a multicenter and retrospective study in six major hospitals of northeast France. The cohort was composed of patients hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Similar to the study of Tonduangu et al ( 22 ) who reported higher values of CRP/Ly in severe clinical features group compared to the moderately ill group of patients (163.9 vs 83.0, p < 0.001), we noticed higher values of this HDR in a line with severity of the disease (61.49 vs 28.56, p < 0.001). The ratio was observed to have better sensitivity during the acute phase, but may be useful as a prognostic biomarker in predicting severity and mortality associated with COVID-19 infection ( 22 ). By reviewing the literature, we noticed that the ratio of lymphocytes and CRP was not given special attention.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the study of Tonduangu et al ( 22 ) who reported higher values of CRP/Ly in severe clinical features group compared to the moderately ill group of patients (163.9 vs 83.0, p < 0.001), we noticed higher values of this HDR in a line with severity of the disease (61.49 vs 28.56, p < 0.001). The ratio was observed to have better sensitivity during the acute phase, but may be useful as a prognostic biomarker in predicting severity and mortality associated with COVID-19 infection ( 22 ). By reviewing the literature, we noticed that the ratio of lymphocytes and CRP was not given special attention.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that numerous diseases are associated with these inflammatory parameters. The acute intracerebral hemorrhage patients with higher MHR values were associated with an increased risk of disability or death according to research by Usta et al 12 Wang 32 and Tonduangu 34 also proved that NHR and CLR could predict the severity and mortality associated with SARS-CoV-2 infection. And CAR is an easily available and independent prognostic marker in locally advanced Non-Small Cell Lung Cancer after CRT.…”
Section: Discussionmentioning
confidence: 90%
“…Recently, monocyte to high-density lipoprotein cholesterol ratio (MHR), neutrophils to high-density lipoprotein cholesterol ratio (NHR), C-reactive protein-to-lymphocyte ratio (CLR), and C-reactive protein-to-albumin ratio (CAR) have attracted extensive attention. Elevated MHR, 12,28,29 NHR, [30][31][32] CLR, [33][34][35] and CAR [36][37][38] have been proved to be related to numerous disorders. However, to date, there is no literature on an association between MHR, NHR, CLR and CAR, and APTB-T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that patients with NLR ≥ 2.6937 were at high risk with the potential to develop worsened and serious clinical outcomes [ 22 ]. In previous study, the cutoff value for CLR ≥ 78.3 can be regarded as patients with severe disease, and ≥ 159.5 can predict mortality [ 15 ]. Together with our study, the NLR and CLR showed the most consistent results across studies in predicting COVID-19 disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several emerging biomarkers such as neutrophil to lymphocyte ratio (NLR) [ 1 , 13 ], platelet to lymphocyte ratio (PLR) [ 14 ] and C-reactive protein to lymphocyte ratio (CLR) [ 15 ] were used to assess COVID-19 progression and were more specific in the early triage of admission than was routine laboratory testing [ 16 ]. Many patients with mild symptoms can potentially progress to severe or critical stages and have different management with oxygen support [ 3 ]; therefore, a simple and efficient predictor is vital to provide increased attention care to reduce the mortality of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%